2021
DOI: 10.1101/2021.06.17.21259098
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pneumocytes are distinguished by highly elevated expression of the ER stress biomarker GRP78, a co-receptor for SARS-CoV-2, in COVID-19 autopsies

Abstract: Vaccinations are widely credited with reducing death rates from COVID-19 but the underlying host-viral mechanisms/interactions for morbidity and mortality of SARS-CoV-2 infection remain poorly understood. Acute respiratory distress syndrome (ARDS) describes the severe lung injury, which is pathologically associated with alveolar damage, inflammation, non-cardiogenic edema, and hyaline membrane formation. Because proteostatic pathways play central roles in cellular protection, immune modulation, protein degrada… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…In conclusion, GRP78 is a pro-viral protein that is upregulated during SARS-CoV-2 infection, as observed here and in other studies in vitro [10][11][12] and in patient tissues and serum 13,14 . Thus, we hypothesize that anti-GRP78 agents in combination with anti-SARS-CoV-2 therapeutics, could further suppress SARS-CoV-2 infection since GRP78 inhibition can deprive the virus of an essential chaperone for their entry and viral protein production.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…In conclusion, GRP78 is a pro-viral protein that is upregulated during SARS-CoV-2 infection, as observed here and in other studies in vitro [10][11][12] and in patient tissues and serum 13,14 . Thus, we hypothesize that anti-GRP78 agents in combination with anti-SARS-CoV-2 therapeutics, could further suppress SARS-CoV-2 infection since GRP78 inhibition can deprive the virus of an essential chaperone for their entry and viral protein production.…”
supporting
confidence: 88%
“…In primary human lung microvascular endothelial cells, MERS-CoV infection led to a substantial increase in GRP78 protein level at 24 hpi 12 . Importantly, autopsy analysis of lungs from COVID-19 patients and non-COVID-19 controls showed that pneumocytes from SARS-CoV-2-infected lungs exhibited robust in situ GRP78 immunostaining compared with that from uninfected controls 13 . Serum GRP78 levels were also reported to be significantly higher in patients during COVID-19 infection compared to control groups 14 .…”
mentioning
confidence: 99%
“…Until recently, BiP has been defined as a chaperone assisting protein folding and UPR signaling within the ER compartment, however, this multifunctional protein has also been found to translocate to other cell locations expanding its role from an ER stress regulator to a general cellular stress transducer in the cytoplasm, mitochondria, and cell surface 28, 29 . Evidence that cell surface BiP influences ligand and antigen recognition is well documented 30, 70 , especially in COVID19, where BiP recognition by SARS-CoV-2 has been recently demonstrated 32, 71, 72 . This role, together with the fact that BiP reaches the cell surface upon stress stimulus, makes it a strong candidate to link inflammatory extracellular signals and stress in immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Shin et al observed reduced viral replication when Grp78 was inhibited, indicating the significance of ER stress regarding the SARS-CoV-2 pathogenesis [90]. The importance of Grp78 and its upregulation during COVID-19 was further indicated in vivo as its expression was found to be abundant in autopsied lung tissues from COVID-19 patients [91], as well as in hamster lung tissues and human lung organoids infected with SARS-CoV-2 [92]. These findings were also consistent with the protein-protein interaction (PPI) network analysis from Sinha et al, who highlighted that ER stress is a major response for the emergence of post-COVID-19 lung disease [92].…”
Section: Betacoronaviruses: the Case Of Sars-cov-2mentioning
confidence: 98%